2019
DOI: 10.3390/ijms20020360
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of Triptolide in Interrupting the NLRP3 Inflammasome Pathway to Attenuate Cardiac Fibrosis

Abstract: In a previous paper, we reported that triptolide (TP), a commonly used immunomodulator, could attenuate cardiac hypertrophy. This present study aimed to further explore the inhibition of cardiac fibrosis by TP and the possible mechanism from the perspective of the NOD-like receptor protein 3 (NLRP3) inflammasome. Hematoxylin-eosin and Masson’s staining, immunohistochemistry, and immunofluorescence were performed to observe cardiac fibrotic changes in mice and mouse cardiac fibroblasts (CFs). The Western blot, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 28 publications
0
50
0
1
Order By: Relevance
“…This effect (a) enhanced cardiac diastolic and systolic functions, (b) activated the pro-fibrotic tumor growth factor 1 beta (TGF-1β) pathway, (c) suppressed the NLRP3 inflammasome and inflammatory mediators of IL-1β, IL-18, MCP-1, and vascular cell adhesion molecule-1 (VCAM-1), and (d) dose-dependently inhibited macrophage infiltration (29). In a recent study, it has been found to inhibit the NLRP3-TGF1β-Smad pathway, suggesting that this compound might be an alternative option for cardiac fibrosis via targeting the NLRP3 inflammasome (30). Furthermore, it down-regulated NLRP3 by targeting hsa-miR-20b in male C57BL/6 mice and in THP-1 cells (31).…”
Section: Diterpenes Modulate Nlrp3 Inflammasome Pathways: Literaturementioning
confidence: 99%
“…This effect (a) enhanced cardiac diastolic and systolic functions, (b) activated the pro-fibrotic tumor growth factor 1 beta (TGF-1β) pathway, (c) suppressed the NLRP3 inflammasome and inflammatory mediators of IL-1β, IL-18, MCP-1, and vascular cell adhesion molecule-1 (VCAM-1), and (d) dose-dependently inhibited macrophage infiltration (29). In a recent study, it has been found to inhibit the NLRP3-TGF1β-Smad pathway, suggesting that this compound might be an alternative option for cardiac fibrosis via targeting the NLRP3 inflammasome (30). Furthermore, it down-regulated NLRP3 by targeting hsa-miR-20b in male C57BL/6 mice and in THP-1 cells (31).…”
Section: Diterpenes Modulate Nlrp3 Inflammasome Pathways: Literaturementioning
confidence: 99%
“…Cardiac fibrosis is a common feature of many pathological cardiac remodeling. Numerous studies have shown that inhibition of the NLRP3 inflammasome pathway exhibited anti-fibrosis effects (Gan et al, 2018;Qiu et al, 2018;Wan et al, 2018;Pan et al, 2019;Gao et al, 2019). However, recently, Li F. et al (2018) found that NLRP3 deficiency exacerbates cardiac fibrosis and inflammation induced by pressure overload, which was contradictory with the previous studies.…”
Section: Discussionmentioning
confidence: 86%
“…The NLRP3 in ammasome comprises the sensor molecule NLRP3, the adaptor protein ASC, and pro-caspase 1 [26]. Xi-Chun Pan et al [27] found that TP had no in uence on NLRP3 or ASC oligomerization, but that it could inhibit NLRP3 and ASC expression, as well as NLRP3-ASC interactions, to inhibit in ammasome assembly. Melanoma research demonstrated that the development of cancer cells was inhibited by reduced in ammasome and IL-1β expression [28].…”
Section: Discussionmentioning
confidence: 99%